2014
DOI: 10.1093/mnras/stu1764
|View full text |Cite
|
Sign up to set email alerts
|

TriAnd and its siblings: satellites of satellites in the Milky Way halo

Abstract: We explore the Triangulum-Andromeda (TriAnd) overdensity in the SPLASH (Spectroscopic and Photometric Landscape of Andromeda's Stellar Halo) and SEGUE (the Sloan Extension for Galactic Understanding and Exploration) spectroscopic surveys. Milky Way main sequence turn-off stars in the SPLASH survey reveal that the TriAnd overdensity and the recently discovered PAndAS stream (Martin et al. 2014) share a common heliocentric distance (D ∼ 20 kpc), position on the sky, and line-of-sight velocity (V GSR ∼ 50 km s −1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
2
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 52 publications
7
65
2
2
Order By: Relevance
“…In contrast, as an example of substructure that is dynamically cold in LOS velocity, an approximate CDF for the Triangulum-Andromeda Stream (TriAnd; located along the LOS toward M31) is shown in red (v 0 ∼50 km s −1 , σ∼15 km s −1 ; e.g., Deason et al 2014;Sheffield et al 2014). D13 suggested that the presence of a cold stream or TriAnd could be the reason for the relative increase in tangential pressure seen in this sample.…”
Section: And Emsellem (2004)mentioning
confidence: 87%
“…In contrast, as an example of substructure that is dynamically cold in LOS velocity, an approximate CDF for the Triangulum-Andromeda Stream (TriAnd; located along the LOS toward M31) is shown in red (v 0 ∼50 km s −1 , σ∼15 km s −1 ; e.g., Deason et al 2014;Sheffield et al 2014). D13 suggested that the presence of a cold stream or TriAnd could be the reason for the relative increase in tangential pressure seen in this sample.…”
Section: And Emsellem (2004)mentioning
confidence: 87%
“…This suggests that there may actually be an association between the MW stream and TriAnd1 and/or TriAnd2. The recent work of Deason et al (2014) further suggests a common origin between the TriAnd1/TriAnd2 features and the PAndAS MW stream.…”
Section: The Pandas "Field Of Streams"mentioning
confidence: 90%
“…The properties of the individual satellites are also interesting in their own right as they could hold important clues on the group preprocessing that most dwarf galaxies are thought to have experienced before being accreted onto a more massive host (e.g., Deason et al 2014;Wetzel et al 2015 for the massscale relevant here). Work has only just started to better characterize the new systems (e.g., Kirby et al 2015;Simon et al 2015;Walker et al 2015aWalker et al , 2015b and, in particular, to understand which are dark-matter-dominated dwarf galaxies, which are globular clusters, and how the dynamical LMC-SMC group environment has affected them.…”
Section: Introductionmentioning
confidence: 99%